2016
DOI: 10.2138/am-2016-5574
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of alunite in Cross crater, Terra Sirenum, Mars: Evidence for acidic, sulfurous waters

Abstract: Cross crater is a 65 km impact crater, located in the Noachian highlands of the Terra Sirenum region of Mars (30°S, 158°W), which hosts aluminum phyllosilicate deposits first detected by the Observatoire pour la Minéralogie, L'Eau, les Glaces et l'Activitié (OMEGA) imaging spectrometer on Mars Express. Using high-resolution data from the Mars Reconnaissance Orbiter, we examine Cross crater's basin-filling sedimentary deposits. Visible/shortwave infrared (VSWIR) spectra from the Compact Reconnaissance Imaging S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 100 publications
(136 reference statements)
0
30
0
Order By: Relevance
“…Although no evidence of life has been found on Mars to date, several observations have suggested that past life may have been possible. Minerals that form on Earth from water, such as chlorides, iron oxides, and sulfates, including hydrated forms of such minerals, such as gypsum, have been found on Mars (e.g., Clark and Van Hart, 1981;Burns, 1987;Klingelhöfer et al, 2004;Clark et al, 2005;Osterloo et al, 2008;Farrand et al, 2009;Glotch et al, 2010;Ehlmann et al, 2016). Terrestrial life is found in the same places as terrestrial water; even the most extreme aqueous environments on Earth, such as acid brine lakes, hot springs, subglacial lakes, and deep ocean trenches, host life (i.e., Mikucki et al, 2010;Zaikova et al, 2018).…”
Section: Overview Of Search For Life On Marsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no evidence of life has been found on Mars to date, several observations have suggested that past life may have been possible. Minerals that form on Earth from water, such as chlorides, iron oxides, and sulfates, including hydrated forms of such minerals, such as gypsum, have been found on Mars (e.g., Clark and Van Hart, 1981;Burns, 1987;Klingelhöfer et al, 2004;Clark et al, 2005;Osterloo et al, 2008;Farrand et al, 2009;Glotch et al, 2010;Ehlmann et al, 2016). Terrestrial life is found in the same places as terrestrial water; even the most extreme aqueous environments on Earth, such as acid brine lakes, hot springs, subglacial lakes, and deep ocean trenches, host life (i.e., Mikucki et al, 2010;Zaikova et al, 2018).…”
Section: Overview Of Search For Life On Marsmentioning
confidence: 99%
“…Terrestrial acid brines, such as modern acid saline lakes on the Yilgarn Craton in Western Australia and volcaniclastic-hosted acid salars in northern Chile, precipitate an unusual suite of minerals, including halite, gypsum and other sulfate salts, iron oxides, jarosite, alunite, kaolinite and other clay minerals, and opalline silica (e.g., Risacher et al, 2002;Benison et al, 2007;Story et al, 2010;Karmanocky and Benison, 2016). These same minerals are found in several places on Mars, including Meridiani Planum, Gusev Crater, and Gale Crater (e.g., Burns, 1987;Klingelhöfer et al, 2004;Madden et al, 2004;Clark et al, 2005;Bibring et al, 2006;Osterloo et al, 2008;Farrand et al, 2009;Glotch et al, 2010;Ehlmann et al, 2016). For these reasons, as well as for their thermochemical stability in Martian conditions, acid brines have been proposed as a likely past liquid on Mars (Burns, 1994;Clark, 1994;Benison and LaClair, 2003;Squyres et al, 2004;Benison and Bowen, 2006;Benison et al, 2008b).…”
Section: The Case For Acid Brines On Marsmentioning
confidence: 99%
“…Alunite is a hydroxylated aluminum sulfate mineral (KAl 3 (SO 4 ) 2 (OH) 6 ) which forms in acidic conditions, either connected to magmatic fluids or as a product of acidic alteration (Ehlmann et al, , and references therein). The detection of alunite and its discrimination from other phases relies on detection of an absorption at 2.17 μm, a doublet at 1.43 and 1.48 μm, and weaker absorptions at 1.76, 2.32, and 2.52 μm (e.g., Swayze et al, ).…”
Section: Assessment Of Previous Mineral Detections Using the 21‐μm Rmentioning
confidence: 99%
“…The detection of alunite and its discrimination from other phases relies on detection of an absorption at 2.17 μm, a doublet at 1.43 and 1.48 μm, and weaker absorptions at 1.76, 2.32, and 2.52 μm (e.g., Swayze et al, ). We examined all three alunite detections currently reported in the peer‐reviewed literature: the CRISM‐type spectral region (Viviano‐Beck et al, 2014; Ehlmann et al, ), a second region from Ehlmann et al ()/Carter et al (), and the mixed alunite deposit in Wray et al (). For all three exposures, we found that alunite's diagnostic absorptions persisted in both ratioed I/F and ratioed radiance data (Figures S8–S10).…”
Section: Assessment Of Previous Mineral Detections Using the 21‐μm Rmentioning
confidence: 99%
“…Mars has been of key importance in the search for extraterrestrial life for decades now (Gargaud et al, 2011). During its geological history there were periods when the planet likely had lakes (Cabrol and Grin, 1999, Ehlmann et al, 2016, Fassett and Head, 2008, rivers or maybe even larger bodies of liquid water (Tokano, 2005). A recent discovery of organic molecules found at Gale crater provided further arguments that Gale crater was potentially habitable about 3.5 billion years ago (Kate, 2018).…”
Section: Introductionmentioning
confidence: 99%